Study Comparison between Alcoholic Extract of Broccoli, Folic Acid and Ferrous Sulfate Against Damage of the Cardiovascular System Induced by Lead-acetate in Rabbits - Dina S Dheyab; Jawad K Arrak; Majida A J Al-Qayim (Ibn Al-Haitham Journal for Pure and Applied Sciences)
Anemia is a most common blood disorder that contributes to Cardiovascular diseases. It is associated with red blood cell dysfunction and compensatory vascular and cardiac endothelial nitric oxide synthase activity enhancement. The present study aimed to investigate the role of broccoli, folic acid, and ferrous sulfate in treating cardiovascular damage induced by lead acetate. Twenty-five female local rabbits 5 months in age with a verge of  weighing 1500 Kg were divided into 5 randomized groups: 1st as a control group (C) and the other four groups 2nd(lead acetate ),3rd(T1F),4th(T2FS),5th(T3B) were exposed to lead acetate 10 mg/kg/Bw/daily for 4 weeks , the second group continued to receive a lead for 8 weeks, while 3rd,4th, and 5th treated with alcoholic extract of the broccoli, folic acid and ferrous sulfate respectively. Blood samples were taken after the 4th and 8th weeks of the experimental period to examine Troponin I, platelets count, and prothrombin time. Heart tissue obtained to examine the histopathological changes. The results after the 4th week in the 2nd,3rd, 4th and 5th groups demonstrated a significant elevation (p≤0.05) in Troponin I, and platelets count while at the 8th week of the treatments, the mean values of Troponin I and platelets count reduced significantly(p≤0.05) .On the contrary, prothrombin time significantly (p≤0.05) decreased in the 4th week of exposed lead acetate  and significantly(p≤0.05) increased in T1F,T2FS,T3B at the 8th week of the treatments. Heart histopathological alterations also were observed in the (lead acetate),(T1F),(T2FS) and (T3B) groups and were repaired to normal  by the treatments. In conclusion, the treatments of the alcoholic extract of Brassica olecera, folic acid, and ferrous sulfate confirmed the superiority of the Brassica olecera in treating the pb-acetate adverse effects on the cardiovascular system, which contributed to its phytochemical and nutrient value.